Tracking under-reported financial flows: China's development finance and the aid-conflict nexus revisited - Austin M. Strange; Bradley Parks; Michael J. Tierney; Andreas Fuchs; Axel Dreher (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
China's provision of development finance to other countries is sizable but reliable information is scarce. We introduce a new open source methodology for collecting project-level development finance information and create a database of Chinese official finance to Africa from 2000 - 2011. We find that China's commitments amounted to approximately US 73 billion, of which US 15 billion are comparable to Official Development Assistance following OECD definitions. We provide details on 1,511 projects to 50 African countries. We use this database to extend previous research on aid and conflict, which suffers from omitted variable bias due to the exclusion of Chinese development finance. Our results show that sudden withdrawals of "traditional" aid no longer induce conflict in the presence of sufficient alternative funding from China. Our findings highlight the importance of gathering more complete data on the development activities of "non-traditional donors" to better understand the link between aid and conflict.
Keywords: F35; F51; D74; 330; Development Finance; Foreign Aid; Non-DAC Donors; South-South Cooperation; China; Africa; Aid Shocks; Violent Armed Conflict; Civil War; Intrastate War